A Literature Review of Various Approaches, Conditions, and Factors That Become Earning Management Motives - Hendry Kurniawan; Ahmad Syifaudin; Nurasiah Nurasiah; Hanif Rani Iswari (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to understand both the company's internal and external conditions that affect earnings management actions as well as approaches to earnings management. The approach in this study uses a qualitative descriptive approach. The approach used in this research is to use a literature review approach. The results show that from 10 previous studies both national and international, earning management is a manager's effort to produce financial figures that are not accurate in order for the manager's financial performance to appear good to shareholders. Earnings management is linked to one of the great theories, agency theory. Taking a bath, income minimization, income maximization, and income smoothing are four patterns of earning management that are well-known. Real earnings management and accrual earnings management are two strategies that are frequently employed in earnings management. Earning management is also influenced by the company's financial and non-financial conditions. However, several previous studies have different results with various explanations. It is known that this difference is caused by different periods, company objects and different research backgrounds.